2002
DOI: 10.1080/00221320209598676
|View full text |Cite
|
Sign up to set email alerts
|

Thinking Styles and Cognitive Development

Abstract: Using R. J. Sternberg's (1988, 1997) theory of thinking styles and W. G. Perry's (1970) theory of cognitive development, the author investigated the nature of thinking styles as they relate to cognitive development. Eighty-two Hong Kong university students (44 male, 38 female) responded to the Thinking Styles Inventory (R. J. Sternberg & R. K. Wagner, 1992) and the Zhang Cognitive Development Inventory (L. F. Zhang, 1997). Statistical analyses provided varying degrees of support for the prediction of an overla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(91 citation statements)
references
References 51 publications
5
80
1
5
Order By: Relevance
“…Para las trece escalas del cuestionario se tiene una coherencia interna que va de 0,57 a 0,88 con una mediana de 0,82 (6). El cuestionario ha sido utilizado en varios lugares del mundo para el desarrollo de investigaciones (6,9,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Este mismo cuestionario también es utilizado en el Perú por algunos docentes universitarios como los de la Facultad de Educación de la Universidad Peruana Cayetano Heredia.…”
Section: Materiales Y Métodosunclassified
See 1 more Smart Citation
“…Para las trece escalas del cuestionario se tiene una coherencia interna que va de 0,57 a 0,88 con una mediana de 0,82 (6). El cuestionario ha sido utilizado en varios lugares del mundo para el desarrollo de investigaciones (6,9,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Este mismo cuestionario también es utilizado en el Perú por algunos docentes universitarios como los de la Facultad de Educación de la Universidad Peruana Cayetano Heredia.…”
Section: Materiales Y Métodosunclassified
“…Desde los inicios de la teoría del autogobierno mental se han realizado estudios que han contribuido al desarrollo de esta teoría, estos estudios se han realizado en diferentes realidades y países de la mayoría de continentes del mundo, pero ninguno en estudiantes de medicina (6,9,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Introductionunclassified
“…Scientific research identified two distinct groups of people whose thinking styles, and therefore also learning needs, are antipodal; analytics (left brained) and holistics (right-brain processors). Convington (1984), Gee (1990), Dille and Mezack (1991), Gibson and Graff (1992), Richardson (1994), Riding and Grimley (1999), Cassidy and Eachus (2000), Zhang (2002) demonstrated that the style of learning and thinking do affect the academic performance of the learners. Grigorenko and Sternberg (1997), Garcia and Hughes (2000) found significant correlations between academic achievement and thinking styles.…”
Section: Styles Of Learning and Thinkingmentioning
confidence: 99%
“…In the studies, thinking styles based on the theory of MSG were examined in relation to learning approaches (Zhang and Sternberg, 2000), learning styles (Cano-Garcia and Hewitt Hughes, 2000), personality types (Balk›s and Ifl›ker, 2005;Zhang, 2001a), teaching approaches (Duman and Çelik, 2011;Zhang, 2001b), self-esteem (Zhang, 2001c;Zhang and Postiglione, 2001), academic achievement (Bulufl, 2006;Grigorenko and Sternberg, 1997;Zhang, 2004b;Zhang and Sternberg, 1998), cognitive developmental levels (Zhang, 2002a), modes of thinking (Zhang, 2002b), critical thinking dispositions (Emir, 2013;Zhang, 2003), students' preferences for teaching styles and students' conceptions of effective teachers (Zhang, 2004a), self regulated learning strategies and motivation towards mathematics (Akkufl ‹spir, Ay and Sayg›, 2011), locus of control (Baflol and Türko¤lu, 2009) and social skill levels (Y›ld›z, 2012).…”
Section: S Smentioning
confidence: 99%